Course “History & Philosophy of Science” for Doctoral Programs in Education and Pedagogical Sciences - Albina R. Sadyikova; Eleonora K. Nikitina; Andrey V. Korzhuev; Yuliya B. Ikrennikova (Высшее образование в России)
Russian pedagogical community has recently faced a new challenge generated by the introduction of emerging conceptual framework for doctoral education treated as the third level of higher education system. The framework for doctoral education covers some typical study programs such as “Methods & technics of pedagogical research” as well as some new ones, including “Academic writing” and competence-based teaching for the traditional postgraduate training. Our argument concerns the course syllabus “History & philosophy of science” aimed at developing the research skills of doctoral students in education. This course is an integral part of the emerging system for doctoral training in Russia. We analyze some philosophical foundations of contemporary pedagogical science, including logical empiricism, Popper’s falsifiability, Paradigm Thesis by Thomas Kuhn, science theories by Paul Feyerabend and Stephen Toulmin, as well as correspondence, pragmatic, conventional and coherent theories of truth. We examine the impact of philosophy of science on methodology of pedagogical education in the context of the history of pedagogical thought. Our conclusion is that despite their poor logical conditions, pedagogical science and research methods benefit from the ideas of philosophy of science that also contributes greatly to the subfield of pedagogical methodology. We seek to optimize the study program of doctoral training syllabus “History and philosophy of science” for doctoral students in education.